Pengaruh ESG Disclosure, Retention Ratio, dan Likuiditas pada Nilai Perusahaan: Peran Moderasi Ukuran Perusahaan di Sektor Infrastruktur (2021–2023) - asyifa, Ade julia; Wahyu Cahyaningtyas, Niken; Utami, Yuni (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2025)
This study analyzes the efect of ESG Disclosure, Retention Ratio, and Liquidity on Firm Value, with Firm Size as a moderator, in Indonesian infrastructure companies (2021-2023). Using 109 observations. Results show ESG Disclosure and Liquidity negatively affect firm value, while Retention Ratio has no significant effect. Firm Size moderates the ESG Disclosure on firm value link but not the others. These findings highlight the importance of ESG and liquidity management, with firm size influencing only ESG’s effect, contributing to stakeholder and signaling theories in firm valuation